Understanding of initial unstable contact behaviors of Au-to-Au microcontact under low contact force for micro- and nano-electromechanical system devices - Qiu, Haodong (2013)
The Au-to-Au micro/nano-contact behavior in unstable contact region during the initial stage of contact formation has been experimentally investigated under low contact force. The experimental results reveal that the asperity deformation process, which is conventionally observed in the stable region, could start from the early stage of contact formation in the unstable region. The fundamental mechanism for the instability of electrical conductance in the unstable region can be explained under a framework of trap-assisted tunneling at the contact interface.